PENERAPAN NILAI-NILAI PENDIDIKAN AGAMA ISLAM DI MTS SWASTA ISLAMIYAH BELONGKU KABUPATEN LABUHAN BATU UTARA - Nurul Mujahidah (Pascasarjana UIN Sumatera Utara, 2017)
Abstract Islamic education is needed by human to persisted in the way of Allah by referring to alquranand hadith. For teenagers, in order to they are not wrong in the act, madrasah can be one of thesolution to lay the value of Islamic education. However, it cannot be denied, although the educationalsystem have set well, there are still the students who can not be controlled He is from various factors,either internal factors and external factors. It can be seen from the problems that exist in many schoolsand madrasah such as smoking, truancy, indecent, courtship and even marriage by accidents, occurebecause of wrong association. It is clearly that these behavior violate the rules of school / madrasah andeven the Islamic value. These also happened in Islamic Private Junior High School Islamiyah BelongkutLabuhan Batu Utara Regency. Based on the background above, it was found the results of research 1)The role of Islamic education teachers in particular and madrasah staff in general have not been appliedthe values of Islamic education maximally yet 2 ) Basically, the aspects that become obstacles in theimplementation of Islamic education values are the staff of the education are not yet mature, teachercompetence, incomplete facilities and infrastructure and low interest, motivation, and the lack of studentreligious provision in the emplementation of Islamic eduaction. 3) As for the solution offered by researcherin the implementation of Islamic eduation values totally are by teacher competence training or workshop,integration-interconnection learning, values which is taught, computer-based learning, giving studentsa daily-life notebook, providing a community, giving a role model, making habits, choosing a childenvironment, creating a conducive environment, and reward and punishment.